2015
DOI: 10.1161/circresaha.116.305557
|View full text |Cite|
|
Sign up to set email alerts
|

“String Theory” of c-kit pos Cardiac Cells

Abstract: Although numerous preclinical investigations have consistently demonstrated salubrious effects of c-kitpos cardiac cells administered after myocardial infarction, the mechanism of action remains highly controversial. We and others have found little or no evidence that these cells differentiate into mature functional cardiomyocytes, suggesting paracrine effects. In this review, we propose a new paradigm predicated on a comprehensive analysis of the literature, including studies of cardiac development; we have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
81
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 106 publications
(316 reference statements)
4
81
0
2
Order By: Relevance
“…This finding led the authors to conclude that cKit + cardiac cells “ may be dedicated vascular endothelial progenitor cells…[not] capable of regenerating the heart with new contracting myocardium to a physiologically meaningful extent ” 11 . However, since cKit expression occurs in several cardiac and extra-cardiac cell lineages 27 , the role and identity of cardiac cKit + cells remained elusive. Do the endothelial cells and cardiomyocytes arise from the same cKit -expressing lineage, or are there multiple cKit + lineages in the heart?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding led the authors to conclude that cKit + cardiac cells “ may be dedicated vascular endothelial progenitor cells…[not] capable of regenerating the heart with new contracting myocardium to a physiologically meaningful extent ” 11 . However, since cKit expression occurs in several cardiac and extra-cardiac cell lineages 27 , the role and identity of cardiac cKit + cells remained elusive. Do the endothelial cells and cardiomyocytes arise from the same cKit -expressing lineage, or are there multiple cKit + lineages in the heart?…”
Section: Introductionmentioning
confidence: 99%
“…Do the endothelial cells and cardiomyocytes arise from the same cKit -expressing lineage, or are there multiple cKit + lineages in the heart? 27 Why do cKit + cells differentiate into far fewer cardiomyocytes than endothelium? Are they bona fide cardiovascular progenitors or do they represent non-cardiomyogenic cells that stochastically (trans)differentiate into myocardium?…”
Section: Introductionmentioning
confidence: 99%
“…Ex vivo manipulation of this cardiac stem cell population unequivocally has demonstrated the repair potential of these cells following adoptive transfer in pathological heart tissue in a variety of small 2 and large animal models 3 . That being said, the controversy has been the true identity of a putative cardiac stem cell as recent studies have shown that this cell in question does not have significant cardiomyocyte forming potential and although it may have exogenous repair processes, its endogenous repair potential is not robust 4 . The presented notion in 2003 was that the tyrosine kinase protein CD117 or c-kit was a bona fide marker to identify and study resident cardiac stem cells and these cells were an endogenous cardiac precursor cell (CPC) in the adult heart 1 .…”
mentioning
confidence: 99%
“…It is critical to point out that all of these studies do not take away from studies explicitly showing that adoptive transfer of exogenously expanded and maintained c-kit+ CPCs can restore cardiac function in a damaged heart as a consequence of forming cardiomyocytes, endothelial and smooth muscle cells along with the ability to release paracrine mediators at the site of injury 4, 16 . The well-documented efficacy of exogenous CPCs and the recent availability of these novel lineage tracing mice models provided the perfect opportunity to develop a system assessing exogenous CPCs ability to form cardiac lineages to endogenous c-kit precursors.…”
mentioning
confidence: 99%
See 1 more Smart Citation